Educar pela pesquisa em ciências na prática de pesquisa no PPGEDUCEM/PUCRS : revisão de dissertações com olhar epistemológico - Paula, Adriana Chilante de (2014)
This dissertation, in the line of Education by Research (EPP) presents the results of qualitative desk research performed in nine dissertations within the Graduate Program in Science and Mathematics Education of Pontifical Catholic University of Rio Grande do Sul (PPGEDUCEM/PUCRS), where the EPP is used how a basis for conducting learning activities in science classes of elementary or secondary school. Your goal is to understand under methodological and epistemological view how Education by Research is operationalized in the research master's science education degree. The methodology for data analysis is the Textual Discourse Analysis (DTA) based on Galiazzi and Moraes (2011). The theoretical foundation presents the characteristics of the EPP and a historical, epistemological, and identities discussion. The results of the desk research showed that the EPP appears being applied by the subjects from a motivation to rebuilding of the teaching practice and the school. There are a theoretical framework based on reference s authors of science education research and a consistent relationship between theories and learning and epistemological conceptions. The contents are contextualized and meaningful for the students which are develop in a political and sociological approach, beyond the conceptual and propedeutics views. The teaching strategies are Learning Units which are to comply with the methodology suggested by the EPP. From the epistemological point of view, in general, there is a consistency with the EPP.